Analysis Of Modifiable Risk Factors For The Incidence Of Hypertension In Adults (18–65 Years) In Students Of The Public Health Science Study Program, University Of Jambi - Tari Indah Lestari; Dwi Noerjoedianto; M. Ridwan; Budi Aswin; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is a non-communicable disease that is a major risk factor for cardiovascular disease and is often unaware of it. Adult age groups, including college students, are at risk of developing hypertension due to lifestyle changes and stress-inducing academic stress. This study aims to determine the determinants of risk factors that can be modified for the incidence of hypertension in students of the Public Health Sciences Study Program, University of Jambi. This study uses a quantitative approach with a cross sectional design. The sample amounted to 60 respondents who were selected using the purposive sampling technique. The variables studied included obesity, smoking behavior, stress levels, and sodium consumption. Data were collected through questionnaires and analyzed univariate and bivariate. The results showed that the majority of respondents had normal nutritional status (93.3%), non-smoking (96.7%), and normal sodium consumption (98.3%). The prevalence of hypertension is only 1.7%. However, the stress level is quite high, which is 53.3%. Stress factors are the most dominant determinants compared to other factors. The conclusion of this study shows that although physical factors are relatively controlled, psychosocial factors such as stress play an important role in the potential occurrence of hypertension. Therefore, promotive and preventive interventions are needed, especially in stress management in students.